Eksperimen Penggunaan Video Pembelajaran Untuk Meningkatkan Kemampuan Menggambar Ilustrasi Siswa Kelas VIII Sekolah Menengah Pertama - Evelyn M. T. Ambarita; Khaerul Saleh (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to improve the illustration drawing skills of class VIII students by using learning videos during online learning. Providing learning videos in the learning process is used as a medium that helps students improve their abilities in learning to draw illustrations. The learning video will explain the theory and the process of drawing illustrations. This research is quantitative by using experimental research using the One-Group Pretest – Posttest Design. In this design, data collection will be carried out with only one group without using a comparison, which will be given a pretest, treatment (behavior) and posttest to determine the improvement that occurs after being given a learning video. The research population is class VIII SMP Negeri 40 Medan with a sample of 62 students. The data obtained will be processed with SPSS 20. The results showed that there was an increase in the ability to draw illustrations in the experimental class using learning videos, with an average pretest score of 75.55 and posttest 85.97. The results show that Ha is accepted which can be seen from the value of tcount 13.621 > ttable 2.042, so that it is obtained that there is an effect of learning videos in the experimental class in improving the ability to draw illustrations.